Insights on Spectrum Sharing in Heterogeneous Networks with Small Cells - Silva, Bruno C. (2018)
This work explores the viability of 5G New Radio spectrum sharing in Ultra High Frequency (UHF), Super High Frequency (SHF) and millimetre wavebands(mmWaves) in outdoor environments. In the mmWaves the linear cellular topology is considered while in the UHF/SHF bands cells with hexagonal shape are assumed. Performance evaluation includes the study of the behaviour of PHY and supported throughput for 2.6, 3.5, 28, 38, 60 and 73 GHz. While the two-slope model is considered for the 2.6 and 3.5 GHz frequency bands, the modified Friis propagation model, with shadow fading, and different values for the standard deviation, is the considered in the millimeter wavebands. With sharing, lower system capacity is supported. We clearly observe that, for coverage distances up to circa 100 m, the supported throughput is higher at the millimetre wavebands, mainly due to the reduction that characterizes the application of the two-slope propagation model at the UHF/SHF bands.